Acanthosis nigricans - a common significant disorder usually unassociated with malignancy - Edmund J. Janniger; Robert A. Schwartz (Termedia Publishing House, 2011)
Acanthosis nigricans (AN) can be a highly significant cutaneous findingand is usually unrelated to cancer. It is most often evident as velvetythickening of axillae, posterior neck fold, flexor skin surfaces andumbilicus. It is common in obesity, which is seen increasing in childrenand adolescents, and can serve as a cutaneous marker of insulin resistance.It is most often associated with hyperinsulinemia, which mayresult from insulin receptor gene defects causing insulin resistance, andless frequently due to mutations in fibroblast growth factor receptors.In this work non malignancy-associated AN types will be emphasized,particularly the association of AN with insulin-resistance, itself a potentialthreat to life.